M1 macrophage-derived extracellular vesicle containing tsRNA-5006c promotes osteogenic differentiation of aortic valve interstitial cells through regulating mitophagy - Xia, Hao; Gao, Mingjian; Chen, Jun; Huang, Guanshen; Xiang, Xiuting; Wang, Yuyan; Huang, Zhaohui; Li, Yongchun; Su, Shuang; Zhao, Zewei; Zeng, Qingchun; Ruan, Yunjun (PeerJ, 2022)
Background Osteogenic differentiation of aortic valve interstitial cells (AVICs) plays a key role in the calcific aortic valve disease progression. Extracellular vesicles (EVs)-derived from M1-polarized macrophages (M1-EVs) orchestrated intercellular communication by delivering non-coding RNAs such as tRNA-derived small RNAs (tsRNAs) is crucial for cardiovascular disease. However, the role and mechanism of M1-EVs tsRNAs in osteogenic differentiation of AVICs remains largely unclear. Methods M1-EVs and PBS treated-RAW 264.7 cell-derived EVs (NC-EVs) were incubated with AVICs and subjected to small RNA sequencing. Candidate tsRNA in M1-EVs was silenced to explore their effects on AVIC osteogenic differentiation and mitophagy. Results DiI-labeled M1-EVs were internalized by AVICs, resulting in significantly increased calcium nodule formation and expression of osteogenesis-related genes in AVICs, including RUNX2, BMP2, osteopontin, and SPP1, compared with NC-EVs. Small RNA sequencing revealed that 17 tsRNAs were significantly up-regulated such as tsRNA-5006c, while 28 tsRNAs were significantly down-regulated in M1-EVs compared with NC-EVs. Intriguingly, tsRNA-5006c-deleted M1-EVs treatment significantly reduced calcium nodule formation and expression of osteogenesis-related genes in AVICs relative to control group. Moreover, target genes of tsRNA-5006c were mainly involved in autophagy-related signaling pathways, such as MAPK, Ras, Wnt, and Hippo signaling pathway. Hallmarks of mitophagy activation in AVICs including mitophagosome formation, TMRM fluorescence, expression of LC3-II, BINP3, and PGC1α, were significantly elevated in the M1-EVs group compared with NC-EVs group, whereas M1-EVs tsRNA-5006c inhibitor led to a significant reduction in these indicators. Conclusion M1-EVs carried tsRNA-5006c regulates AVIC osteogenic differentiation from the perspective of mitophagy, and we provide a new target for the prevention and treatment of aortic valve calcification.
Keywords: Osteogenic differentiation; tRNA-derived small RNA; Extracellular vesicles; Macrophage M1 polarization; Mitophagy